2015
DOI: 10.2967/jnumed.115.156414
|View full text |Cite
|
Sign up to set email alerts
|

Performance of 11C-Pittsburgh Compound B PET Binding Potential Images in the Detection of Amyloid Deposits on Equivocal Static Images

Abstract: The goal of this study was to clarify whether binding potential (BP) images using 11 C-Pittsburgh compound B ( 11 C-PiB) and dynamic PET can reliably detect cortical amyloid deposits for patients whose 11 C-PiB PET static images are ambiguous and whether visual ratings are affected by white matter retention. Methods: Static and BP images were constructed for 85 consecutive patients with cognitive impairment after 11 C-PiB dynamic PET. Cortical uptake was visually assessed as positive, negative, or equivocal fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…LPR corresponded to distribution volume ratio (DVR) of IMZ because delayed IMZ SPECT activity and distribution volume of IMZ SPECT had high linear correlation [11]. BP ND is equal to the DVR minus a value of 1, as described by Innis et al [13, 14]. We compared FMZ BP ND and (LPR-1) of delayed IMZ SPECT (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…LPR corresponded to distribution volume ratio (DVR) of IMZ because delayed IMZ SPECT activity and distribution volume of IMZ SPECT had high linear correlation [11]. BP ND is equal to the DVR minus a value of 1, as described by Innis et al [13, 14]. We compared FMZ BP ND and (LPR-1) of delayed IMZ SPECT (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Interrater disagreement was limited to cases in which it was difficult to judge whether or not one region showed increased accumulation, which is susceptible to interference by non-specific white matter uptake of 18 F-flutemetamol. These instances of disagreements between readers may correspond to equivocal cases in 11 C-PiB PET studies (3,4). Bias in judgment criteria for visually amyloidpositive findings in at least one of the five key regions may tend to lead to deviation from the quantitative measurement in these equivocal cases.…”
Section: Discussionmentioning
confidence: 99%
“…When using amyloid PET in clinical practice, qualitative determination of whether amyloid PET is positive or negative is performed by visual interpretation alone. In this binary classification, equivocal findings are inevitable and lead to interrater variability in visual interpretation (3,4) because each rater has his or her own experience and potential internal criteria. Equivocal findings should be avoided for determining the indication for disease-modifying drugs currently under development.…”
Section: Introductionmentioning
confidence: 99%
“…Generally in PET amyloid imaging, amyloid deposits are mainly evaluated by visual assessment by neuroradiologists. However, it has been reported that in amyloid PET, some equivocal findings are observed in interreading even among experienced neuroradiologists, and for such patients, SUVR tends to take intermediate values ranging from a typical value for AD to that for NL (Hosokawa et al., ; Payoux et al., ). The reason may be because PVE results in lower SUVR values despite sufficient amyloid deposits.…”
Section: Discussionmentioning
confidence: 99%